Effectiveness of Using Electronic Parking Fee System (E-Parking) In Makassar City - Haliah; Nirwana; Dwi Kartika Aulya; Mubdi Dzuwhandy; Anastasia D'Ornay (Universitas Muhammadiyah Makassar, 2025)
This study examines the effectiveness of the Electronic Parking Fee System (E-Parking) implemented by the Makassar City Regional Revenue Agency (BAPENDA) as part of the city’s effort to modernize public services and enhance regional revenue. Using a qualitative research design, data were collected through observations, in-depth interviews with key informants, and document analysis to obtain a comprehensive understanding of the system’s performance. The findings reveal that the adoption of E-Parking has contributed to improved transparency, efficiency, and accountability in parking tax management. The system minimizes manual intervention, reduces the risk of illegal levies, and enhances service quality for parking users. Empirical data show an increase in the number of taxpayers using E-Parking from 29 in 2019 to 35 in 2020, although overall revenue declined due to movement restrictions during the COVID-19 pandemic. Despite the temporary decline, the E-Parking system demonstrates strong potential to optimize regional original income (PAD) by ensuring accurate transaction recording and reducing revenue leakages. Users reported that the system is easier, more secure, and more reliable compared to manual ticketing. Overall, the study concludes that E-Parking is an effective innovation in public service delivery, supporting Makassar City’s transition toward a more transparent and technology-driven governance system.